Cash Flow Valuation of Maruti and Hyundai (An Analytical Perspective) - Ashima; Chitkara, S C (Journal of Commerce and Trade, 2010)
This research paper focuses on an analytical valuation perspective of Maruti Suzuki India Ltd. (MSIL) and Hyundai Motors India Ltd. (HMIL). MSIL is the no. one car maker in India and HMIL takes place second position. The companies were valued on the basis of 9 financial parameters. In the present era of Liberalization, Privatization and Globalization, the Market has become globally competitive; hence the survival of an enterprise depends upon the efficiency and accuracy, it is necessary to evaluate the financial performance of sampled units to know where these companies stand in the market and how these companies can improve further in the future by knowing their shortcomings.